Recontextualizing Cooperative Learning: Indonesian EFL Teachers’ Agency in Adapting a Global Pedagogical Model - Umar Umar; Ismail Ismail (Journal of Education and Learning Sciences, 2026)
Cooperative Learning (CL) is widely recognized as an effective student-centered pedagogical approach and has been extensively promoted in educational reforms worldwide. However, existing studies have predominantly focused on measuring its effectiveness, while limited attention has been given to how teachers interpret and enact CL within their specific sociocultural contexts. Addressing this gap, this study investigates how Indonesian English as a Foreign Language (EFL) teachers conceptualize, implement, and adapt cooperative learning in their classroom practices. Employing a qualitative multiple case study design, data were collected from four secondary school English teachers through semi-structured interviews, classroom observations, and document analysis. The study was informed by Sociocultural Activity Theory and the concept of teacher agency to examine how pedagogical practices are shaped by cultural values, institutional conditions, and professional experiences. The findings reveal that cooperative learning is not implemented as a uniform instructional model but is continuously reinterpreted and recontextualized according to local classroom realities. Teachers enacted CL in diverse ways, drawing upon moral, cultural, religious, institutional, and pragmatic considerations. Furthermore, cultural norms emphasizing social harmony influenced interaction patterns, while tensions between policy expectations and classroom realities prompted teachers to adapt cooperative learning practices strategically. The study highlights teacher agency as a critical mediating factor in translating global pedagogical ideas into contextually meaningful classroom practices. These findings contribute to the literature on pedagogical recontextualization and teacher agency by demonstrating that successful implementation of cooperative learning depends not on procedural fidelity but on teachers’ capacity to adapt pedagogical principles to their sociocultural environments. The study also offers implications for educational policy and teacher professional development by emphasizing the importance of context-sensitive approaches to pedagogical reform.